2020
DOI: 10.1590/s0102-865020200050000008
|View full text |Cite|
|
Sign up to set email alerts
|

Differences in lipidomics may be potential biomarkers for early diagnosis of pancreatic cancer

Abstract: Intellectual, scientific, conception and design of the study; acquisition, analysis and interpretation of data; technical procedures; statistical analysis; manuscript preparation, final approval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…The pancreas was an important organ of lipid metabolism in human body and the study of lipid omics could help to understand the changes of pancreas function. It is reported that the concentration of arachidonic acid, lysophosphatidylcholine, phosphatidylcholine (PC) and phosphatidyl ethanolamine (PE) in the plasma of patients with early pancreatic cancer was found to be increased by the method of lipid group analysis [8,9]. However, lipid metabolites with differences in pancreatic cancer and adjacent tissues were screened out through tissue samples, and the results showed that PC, PE were signi cantly increased in cancer tissues, which was basically consistent with previous plasma studies.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The pancreas was an important organ of lipid metabolism in human body and the study of lipid omics could help to understand the changes of pancreas function. It is reported that the concentration of arachidonic acid, lysophosphatidylcholine, phosphatidylcholine (PC) and phosphatidyl ethanolamine (PE) in the plasma of patients with early pancreatic cancer was found to be increased by the method of lipid group analysis [8,9]. However, lipid metabolites with differences in pancreatic cancer and adjacent tissues were screened out through tissue samples, and the results showed that PC, PE were signi cantly increased in cancer tissues, which was basically consistent with previous plasma studies.…”
Section: Discussionsupporting
confidence: 84%
“…The correlation analysis between the proportion of immune cells and the expression of lipid metabolism genes in tumor microenvironment showed that there were differences in the expression of immune-related lipid metabolism genes, suggesting a potential interaction between lipid metabolism and immune response [20]. Our previous study suggested abnormal lipid metabolism in the serum of pancreatic cancer, and this study further veri ed this study through tissue samples, which laid a foundation for the later study on the molecular mechanism of lipid metabolism and pancreatic cancer [9].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Given the high risk of pancreatic surgery, it was difficult to obtain healthy controls for pancreatic tissue. However, our previous studies showed differences in lipid metabolites between pancreatic cancer patients and healthy controls in blood samples[ 36 ]. In addition, the association between the risk score and immune activity was not further validated in the corresponding experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with high CD36 expression have lower overall survival, and the use of anti-CD36 strategies could represent a promising therapeutic approach. Recently, a clinical investigation using liquid chromatography tandem mass spectrometry (LC-MS/MS) revealed that differences in lipidomics may be potential biomarkers for early diagnosis of pancreatic cancer [ 13 ]. It was found that free fatty acids (FFAs) were significantly decreased in patients with pancreatic cancer.…”
Section: Altered Fatty Acid Metabolismmentioning
confidence: 99%